Case report: Successful treatment with biologics in a pediatric patient with a severe inflammatory skin disease and novel CARD14 mutation - Niedźwiedź, Michał; Narbutt, Joanna; Siekierko, Aleksandra; Skibińska, Małgorzata; Kwiek, Bartłomiej; Sobolewska-Sztychny, Dorota; Ciążyńska, Magdalena; Poznańska-Kurowska, Katarzyna; Gostyński, Antoni; Lesiak, Aleksandra (Frontiers in Medicine, 2024)
CARD14 mutations have been associated with psoriasis vulgaris, psoriatic arthritis, generalized and palmoplantar pustular psoriasis, pityriasis rubra pilaris and atopic dermatitis. We present a pediatric patient with a novel CARD14 mutation, diagnosed with CAPE, CARD14-associated papulosquamous eruption, who was successfully treated with biological treatment.